Comparison of medical management and genetic counseling options pre‐ and post‐whole exome sequencing for patients with positive and negative results. Issue 2 (16th January 2019) - Matias, Margret; Wusik, Katie; Neilson, Derek; Zhang, Xue; Valencia, C. Alexander; Collins, Kathleen
Abstract: Whole exome sequencing (WES) is expected to impact patient management, but data surrounding the types of downstream effects and how frequently these effects are observed depending on the type of WES results received is limited. This study investigated changes to medical management and genetic counseling (GC) options following WES for individuals with positive and negative results. Electronic medical records of patients who had positive ( n  = 37) or negative ( n  = 41) WES results from Cincinnati Children's Hospital were retrospectively reviewed. Pre‐ and post‐WES management and GC options were analyzed as were differences between positive and negative results. Almost all participants (97%) were observed to have at least one difference in medical management and/or GC options following WES. Comparing pre‐ and post‐WES detected significant differences ( p  ≤ 0.05) in genetic testing, imaging, and metabolic testing regardless of WES results. Participants with positive results also had significant differences in recurrence risk, reproductive options, testing for family members, and support groups. Pre‐ to post‐WES differences were significantly different between participants with positive and negative results in specialist referrals, lifestyle recommendations, recurrence risk, and all GC options ( p  ≤ 0.05); specifically, participants with positive results were more likely to have differences in these categories. Overall, differences in medical management and/or GC options were observed for participants with both types of WES results (positive and negative). Results from this study may contribute to the understanding of how WES impacts patients and their care and thus improve its utilization. Abstract :